(untitled) (Global Journal of Human-Social Science, 2021)
In Taiwan the heat island effect is the most significant in Taipei City Thus this research provides a causal explanation for why urban outdoor air temperature has an M-shape EKC pattern for metropolitan areas in a country Results show that the growth rate change in CO2 concentration can induce changes to the periods of the La Nino effect and EI Nino effect causing high fluctuations in rain accumulation The amount of rain then alters A-type evaporation and so the evaporation amount is the top factor for the diffusion of a city s heat This fluctuation plays as a cooling and heating source for the V region of the M shape in the outdoor air temperature EKC pattern In our previous studies the growth rate change in CO2 concentration correlates to the energy structure Therefore a heat sinking model has been proposed to explain the accumulation of heat in a city in which a proportion process for the solar irradiation source from buildings and remodeling engineering from a public housing policy and the private sector can play as a heating source of the two peaks of the M shape and present long-term linear growth in the outdoor air temperature EKC pattern